The Impact of Blockchain on Audit Quality: Field Study (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aims to clarify The Impact of Blockchain on Audit Quality. To achieve the objective of this research, a field study was conducted by using a questionnaire to collect data from the population of the study which is composed of auditors accredited by the Finance Ministry, and authorized to audit shareholding companies. The questionnaire was distributed to 436 out of 493 auditors. 188 copies were returned, and 128 of them were suitable for analysis.The study concluded that there is an impact of  Blockchain on Audit Quality.